MODEL REGRESI LOGISTIK ORDINAL - ANIK PURWANINGSIH, 089711696 (2002)
Ordinal logistic regression model is a logistic regresion model with ordinal responses. the purpose of the skripsi are to determine the parameter estimation in ordinal logistic regresion model and goodness of fit test of models. here, cumulative logit model is used to form ordinal logistic regression model. parameter estimation in ordinal logistic regression use maximum likelihood method. while deviance statistic is used for goodness of fit test the model when the model hold, deviance asymptotic chi-squarred distribution. the application of ordinal logistic regression model in computer program using s-plus show that three example with 3 response categories obtained 2 ordinal logistic regression model for each example goodness of fit test of the models show that only the second example model is fitted